Effects of Age and Military Service on Strength and Physiological Characteristics of U.S. Army Soldiers - Abt, John P.; Perlsweig, Katherine; Nagai, Takashi; Sell, Timothy C.; Wirt, Michael D.; Lephart, Scott M. (Military medicine, 2016)
Soldiers must maintain tactical performance capabilities over the course of their career. Loss in physical readiness may be a function of age and the operational demands associated with increasing years of service. The purpose of this study was to assess strength and physiological characteristics in different cohorts of U.S. Army Soldiers based on years of service and age. A total of 253 Soldiers (age: 28.1 ± 6.8 years; height: 1.76 ± 0.11 m; mass: 84.1 ± 12.2 kg) participated. Individual subject cohorts were created based on years of service (1-5 years, 6-10 years, 11-15 years) and age (20-24 years, 25-29 years, 30-34 years, 35-39 years, 40-44 years). Testing included shoulder, knee, ankle, and torso strength, aerobic capacity/lactate threshold, anaerobic power/capacity, and body composition/total mass. Those with 11 to 15 years of service and between ages 30 and 34 had a higher percentage of body fat, and lower aerobic capacity and lactate threshold than younger Soldiers with fewer years of service. Physical training interventions should focus on maintenance of physiological characteristics to offset the loss of readiness at the similar time point of 11 to 15 years of service and 30 to 34 years of age.